Selecting the Best Waste Disposal Method in Health Using Combined Method of Fuzzy Analytical Hierarchy Process and Fuzzy Weighted Aggregated Sum Product Assessment - Hamzeh Amin-Tahmasbi; Hossein Nasirzadeh (Tehran University of Medical Sciences, 2022)
Background and Aim: Inattention of hospital waste management has caused many problems. As a consequence, it has put the environment and human health at serious risk. Medical centers are one of the important health institutions which in recent years, population growth, increasing clients and service populations has led to significant growth in waste production in them. The quality and quantity of medical centers waste is becoming more and more problematic and is considered as a dangerous toxic substance. The purpose of this article is to evaluate, prioritize and explain the management plan for treatment and disposal of medical centers waste. Materials and Methods: Important criteria in choosing the method of waste disposal of medical centers were extracted from previous studies. Then, the importance of these criteria was determined using the Fuzzy Analytic Hierarchy Process (Fuzzy AHP) and at the end, the best disposal method was selected using the Fuzzy Weighted Aggregated Sum Product Assessment (Fuzzy WASPAS). Results: Among the main criteria, environmental issues was the first priority with 0.517 weight and the criteria of cost and volume of waste with the points of 0.317 and 0.166 were ranked second and third, respectively. Also, between the sub-criteria, the air pollution was ranked first with 0.256 weight. Finally, among the disposal methods, the sanitary landfill method with 0.317 weight was ranked first and the microwave methods, waste incineration and autoclave with the points of 0.265, 0.253, and 0.173 scored second to fourth respectively. Conclusion: Considering the obtained results and prioritizing, it is possible to achieve more risk reduction, reduction of environmental pollution and reduction of costs by disposing of waste in health centers. Accordingly, the most appropriate method for disposing of waste in medical centers in the country is the "sanitary landfill" method. Of course, sanitary landfilling of waste should be done in an appropriate and standard way to prevent groundwater pollution and damage to the environment. Solving the problems caused by hospital waste is a complex and multidimensional issue that requires the cooperation and assistance and integration of community facilities (government, private and public institutions).